Effects of posterior vitreous detachment on aqueous humour levels of VEGF and inflammatory cytokines. Issue 8 (26th February 2015) - Takahashi, Hidenori; Nomura, Yoko; Tan, Xue; Fujino, Yujiro; Kawashima, Hidetoshi; Yanagi, Yasuo
Abstract : Purpose: To investigate the association of posterior vitreous detachment (PVD) with aqueous levels of vascular endothelial growth factor (VEGF) and other inflammatory cytokines. Methods: These are prospective comparative studies. Subjects comprised 98 eyes for VEGF concentration and 80 eyes for other cytokines, which are normal except for cataract. PVD was examined by B-mode ultrasonography, and the subjects were divided into complete PVD group (PVD group) or the other group (without PVD group). At the beginning of cataract surgery, aqueous humour was collected and the concentrations of VEGF and other inflammatory cytokines were determined using ELISA and a multiplex cytokine assay, respectively. The concentrations of these cytokines were compared between the two groups. Results: Complete PVD was observed in 56 (57%) eyes for VEGF concentration analysis, and 51 (64%) eyes for the other cytokines analysis. The concentrations of VEGF, adjusted for the average age, axial length and gender distribution, was 47 pg/mL in the PVD group and 72 pg/mL in the without PVD group. The concentrations of IP-10, MCP-1, CXCL13 and CCL11 were 53, 450, 3.8 and 6.0 pg/mL in the PVD group, and 100, 560, 7.0 and 8.4 pg/mL in the without PVD group, respectively. Multiple regression analysis revealed that the logarithmic concentration of VEGF, IP-10, MCP-1, CXCL13 and CCL11 were significantly lower in the eyes with PVD than in those without PVD independently of age, sex and axial length (p=0.01, p=0.002, p=0.009, 0.006 and 0.03, respectively). Conclusions: PVD is related to the change in the multiple intraocular inflammatory cytokines.